A review of drug therapy for sporadic fatal insomnia. Issue 5 (3rd September 2017) - Tabaee Damavandi, Pardis; Dove, Martin T.; Pickersgill, Richard W.
ABSTRACT: Background : Sporadic fatal insomnia (sFI) is a rapid progressive neurodegenerative disease characterised by gradual to perpetual insomnia, followed by dysautonomia, coma and death. 1 The cause of sFI was recently mapped to a mutation in a protein, the prion, found in the human brain. It is the unfolding of the prion that leads to the generation of toxic oligomers that destroy brain tissue and function. Recent studies have confirmed that a methionine mutation at codon 129 of the human Prion is characteristic of sFI. Current treatment slows down the progression of the disease, but no cure has been found, yet. Methods : We used Molecular Docking and Molecular Dynamics simulation methods, to study the toxic Fatal-Insomnia-prion conformations at local unfolding. The idea was to determine these sites and to stabilise these regions against unfolding and miss-folding, using a small ligand, based on a phenothiazine "moiety". Conclusion : As a result we here discuss current fatal insomnia therapy and present seven novel possible compounds for in vitro and in vivo screening.